Probing Charge Separation in Structurally Different C60/exTTF Ensembles - Díaz, Marta C; Herranz, Ma Angeles; Illescas, Beatriz M; Martín, Nazario; Godbert, Nicolas; Bryce, Martin R; Luo, Chuping; Swartz, Angela; Anderson, Greg; Guldi, Dirk M (Journal of organic chemistry, 2003)
The scope of the present work is to highlight the effects stemming from different C60/exTTF linkages (exTTF = 9,10-bis(1,3-dithiol-2-ylidene)-9,10-dihydroanthracene)either via an anthracene unit or a dithiole ring. Particular emphasis is placed on photoinduced electron-transfer features. Therefore, we devised a new series of C60-exTTF ensembles, synthesized via 1,3-dipolar cycloaddition and Diels−Alder cycloaddition reactions, in which exTTF units are separated from C60 by two single bonds (3a−c, 4), one vinylene unit (5a), or two vinylene units (5b). The cyclic voltammetry reveals an amphoteric redox behavior with remarkably strong electron-donor ability of the trimethyl-substituted exTTF moiety in 4 and 5a,b. Steady-state and time-resolved photolytic techniques show that the fullerene singlet excited state in (3a−c, 4, and 5a,b) is subject to a rapid electron-transfer quenching. The resulting charge-separated states, that is C60 •--exTTF•+, were identified by transient absorption spectroscopy. We determined radical pair lifetimes of the order of 200 ns in benzonitrile. This suggests (i) that the positive charge of the exTTF•+ is delocalized over the entire donor rather than localized on one of the 1,3-dithiole rings and (ii) that linking exTTF via the anthracene or 1,3-dithiole ring has no appreciable influence. Increasing the donor−acceptor separation via implementing one or two vinylene units as spacers led to improved radical pair lifetimes (5a:  τ = 725 ns; 5b:  τ = 1465 ns).